2003
DOI: 10.1046/j.1365-2672.2003.01985.x
|View full text |Cite
|
Sign up to set email alerts
|

Typification of Oenococcus oeni strains by multiplex RAPD-PCR and study of population dynamics during malolactic fermentation

Abstract: This method will be a good tool to study the population dynamics of bacteria during malolactic fermentation and to evaluate the performance of new malolactic starter cultures and their dominance over the native microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 41 publications
(46 reference statements)
3
51
2
Order By: Relevance
“…The different strains present in each region may be responsible for the production of wines with different properties. However, at the level of each wine estate, it is possible that O. oeni strains contribute to the production of specific wines because these strains may persist in the estates for several years (21). This study has also revealed another specific situation concerning some types of wines such as the white and red wines produced in Burgundy.…”
Section: Discussionmentioning
confidence: 72%
“…The different strains present in each region may be responsible for the production of wines with different properties. However, at the level of each wine estate, it is possible that O. oeni strains contribute to the production of specific wines because these strains may persist in the estates for several years (21). This study has also revealed another specific situation concerning some types of wines such as the white and red wines produced in Burgundy.…”
Section: Discussionmentioning
confidence: 72%
“…LAB species were identified by species-specific PCR tests using primers matching the rpoB gene (26). O. oeni strain typing was carried out by using multiplex randomly amplified polymorphic DNA (RAPD)-PCR (25). Eight HDC Ï© O. oeni strains isolated during this work, designated strains A to H, were stored in the IOEB collection under reference numbers IOEB 0605 to IOEB 0612, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This was supported by the levels of DNA-DNA homology and by similarities of the genetic maps of diverse strains (7,50). In addition, differentiation of O. oeni strains can only be achieved by using methods targeting minor genotypic differences: random amplification of polymorphic DNA (RAPD) (36,48,49), DNA fingerprinting (46), amplified fragment length polymorphism (3), or pulsed-field gel electrophoresis (PFGE) patterns of low-frequency restricted genomes (14, 20-22, 38, 45). However, the concept of genetic homogeneity was repeatedly challenged by the detection of groups of strains-often two major groups-distinguished on the basis of molecular and/or phenotypic/metabolic characteristics, leading authors to suggest that O. oeni might be divided into two subspecies (35,45).…”
mentioning
confidence: 99%